Use of microcomputed tomography for the evaluation of canal filling quality depending on the part of root canal* - Jaworska, Małgorzata; Kierklo, Anna (Journal of Stomatology, 2017)
Introduction. High-resolution microcomputed tomography (microCT) is an emerging technology with several applications to endodontics. Aim of the study: To analyse in detail root canal fillings in the apical third, in the middle and coronal thirds in in vitro conditions with the use of microCT. Material and methods. Eighty single roots were prepared with the “step-back” technique or with a Pro File system using the “crown-down” technique. Each main group was divided into two subgroups and obturated with either cold lateral (CL) condensation or thermoplastic (Th) compaction with System B and Obtura II. The distribution of voids (number and volume) was assessed by means of microCT. Results. In the apical third of the root canal, in total over three times more external voids (e-voids) (598) with a greater volume than internal voids (i-voids) (167) were found. In the middle third the numbers of i-voids (664) and e-voids (651) were similar. The mean volume of i-voids was higher among root canals filled using CL condensation as compared to Th compaction (p=0.001). The greatest number of i-voids (3872) and e-voids (1888) were found in the coronal third. The mean volume of i-voids was higher among root canals filled using CL condensation as compared to those filled by means of Th compaction (p=0.001). Conclusions. Irrespective of the obturation methods, the most hermetically filled part of the root canal was the apical third while the coronal third was the least hermetically filled part. E-voids with a greater volume predominated in the apical part, while numerous small i-voids were detected closer to the crown.